1990
DOI: 10.1152/jappl.1990.68.3.876
|View full text |Cite
|
Sign up to set email alerts
|

Xenon kinetics in muscle are not explained by a model of parallel perfusion-limited compartments

Abstract: Experimental tissue gas kinetics do not follow the prediction for a single stirred perfusion-limited compartment. One hypothesis proposes that the kinetics might be explained by considering the tissue as a collection of parallel compartments, each with its own flow, reflecting the tissue microcirculatory flow heterogeneity. In this study, observed tissue gas kinetics were compared with the kinetics predicted by a model of multiple parallel compartments. Gas exchange curves were generated by recording the time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 0 publications
0
31
0
Order By: Relevance
“…From the clearance rate of 133 Xe it is possible to calculate the blood flow (b_f.) in mL 100 g tissue −1 min −1 , when the tissue blood partition coefficient λ is known ( Kety 1951, Novotny et al . 1990 ): where λ is the partition coefficient tissue/blood (in μ C g tissue −1 / μ C mL blood −1 ), which is between 5 and 10 for adipose tissue.…”
Section: Methodsmentioning
confidence: 99%
“…From the clearance rate of 133 Xe it is possible to calculate the blood flow (b_f.) in mL 100 g tissue −1 min −1 , when the tissue blood partition coefficient λ is known ( Kety 1951, Novotny et al . 1990 ): where λ is the partition coefficient tissue/blood (in μ C g tissue −1 / μ C mL blood −1 ), which is between 5 and 10 for adipose tissue.…”
Section: Methodsmentioning
confidence: 99%
“…This approach was followed in a previous analysis of H 2 biochemical decompression in a pig model , from which a single τ for H 2 uptake and elimination of 0.7-2 min was derived, depending on model assumptions. Although experiments have shown that more complex models are required to describe real tissues (Novotny et al, 1990;Himm et al, 1994), the simplicity of a single time constant for estimating the time when tissues reach equilibrium with the ambient pressure is appealing. Years of experience with the maximum likelihood technique have shown that a large number of experiments are necessary to solve problems such as differences in gas potencies for inducing DCS (Lillo, 1988;Lillo and MacCallum, 1991), or asymmetrical exchange kinetics for compression and decompression (Thalmann et al, 1997;Lillo and Parker, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Fahlman et al, (2001) used one exponential time constant to describe the kinetics, which satisfactorily explained the observed DCS incidence. However, since other DCS modelling efforts (Tikuisis et al, 1991;Himm et al, 1994;Lillo et al, 1997;Parker et al, 1998;Lillo and Parker, 2000) and studies using direct physiological or physical measurements of gas fluxes in animals (D'aoust et al, 1976;Novotny et al, 1990) suggest that the uptake and elimination of gases are asymmetrical, we wanted to perform a critical evaluation of our previous model in an attempt to gain further understanding of gas fluxes in hyperbaria. Studying gas kinetics and DCS risk in this data set is particularly interesting because of the combination of gas fluxes occurring during conventional decompression and fluxes due to active metabolism of gas during biochemical decompression.…”
Section: Introductionmentioning
confidence: 99%
“…38,39 Novotny and colleagues found that when inert gas exchange and blood flow distribution to muscle were measured simultaneously, gas exchange was slower than predicted on the basis of the measured flow distribution. 40 The retention of gas in tissue by countercurrent diffusion was a possible explanation for this observation and might be one reason that tissue half-times in decompression models are longer than would be expected on the basis of physiologically reasonable blood flow.…”
Section: Diffusion Between Blood and Tissuementioning
confidence: 99%
“…The Orca EDGE (Electronic Dive GuideExperience), the first commercially successful digital dive computer. The display of the EDGE had a bar graph that represented the computed nitrogen tension (in fsw) in each of 12 Haldane tissues.Figures continued on next pagearterial blood on one face 40. Figure 4-11A shows the nitrogen tension in this tissue slab after a time t 1 at depth during which a nitrogen gradient has developed in tissue.…”
mentioning
confidence: 99%